Database resources of the National Center for Biotechnology Information. Issue Volume 49:Issue D1(2021) (23rd October 2020) - Sayers, Eric W; Beck, Jeffrey; Bolton, Evan E; Bourexis, Devon; Brister, James R; Canese, Kathi; Comeau, Donald C; Funk, Kathryn; Kim, Sunghwan; Klimke, William; Marchler-Bauer, Aron; Landrum, Melissa; et al.
Abstract: The National Center for Biotechnology Information (NCBI) provides a large suite of online resources for biological information and data, including the GenBank ® nucleic acid sequence database and the PubMed ® database of citations and abstracts published in life science journals. The Entrez system provides search and retrieval operations for most of these data from 34 distinct databases. The E-utilities serve as the programming interface for the Entrez system. Custom implementations of the BLAST program provide sequence-based searching of many specialized datasets. New resources released in the past year include a new PubMed interface and NCBI datasets. Additional resources that were updated in the past year include PMC, Bookshelf, Genome Data Viewer, SRA, ClinVar, dbSNP, dbVar, Pathogen Detection, BLAST, Primer-BLAST, IgBLAST, iCn3D and PubChem. All of these resources can be accessed through the NCBI home page at https://www.ncbi.nlm.nih.gov .